Usefulness of The CHADS2 and CHA2DS2-VASc Scores in Predicting In-Hospital Mortality in Acute Coronary Syndrome Patients: A Single-Center Retrospective Cohort Study - Pramudyo, Miftah; Putra, Iwan Cahyo Santosa; Pratama, Fahmi Bagus; Pranata, Raymond (Jurnal Kardiologi Indonesia, 2023)
BackgroundAlthough the GRACE risk score is widely accepted as an established scoring system to predict in-hospital mortality in acute coronary syndrome (ACS) patients, this scoring system still depends on electrocardiography and laboratory findings to determine the results. Therefore, we aim to retrospectively evaluate the association between the CHADS2 and CHA2DS2-VASc score as an anamnesis-only mediated scoring system and in-hospital mortality in hospitalized ACS patients. MethodsThis retrospective cohort study analyzed data of ACS patients from the ACS registry in Dr. Hasan Sadikin Central General Hospital from 2018 to 2021. The outcome of this study was in-hospital mortality. The association between these scoring system and in-hospital mortality were evaluated using binary logistic regression analysis. Receiver operating characteristics (ROC) analysis was also performed to assess the success rate of this scoring system in predicting in-hospital mortality. ResultsA total of 1339 patients were included in this study, and 162 (12.1%) of them died in the hospital. High CHA2DS2-VASc score group (cut-off >2) was significantly associated with higher risk of in-hospital mortality before (OR=2.56 [1.75,3.75]; p<0.001) and after adjustment of several confounding factors (OR=3.39 [1.73,6.64]; p<0.001). Meanwhile, the high CHADS2 score (cutoff >2) was only significantly increased the risk of in-hospital mortality in univariate analysis (OR=2.05[1.47,2.87];p<0.001), but was not significantly associated with in-hospital mortality after multivariate analysis (OR=1.31 [0.92,1.86];p=0.129). ROC analysis revealed that predictive accuracy of CHA2DS2-VASc score was significantly greater compared to CHADS2 score (AUC: 0.653 vs 0.609, p<0.001). However, the predictive value of CHA2DS2-VASc score was significantly lower than the GRACE risk score (AUC: 0.789 vs 0.653, p<0.001). ConclusionOur study showed that the CHA2DS2-VASc score >2 was significantly and independently associated with higher in-hospital mortality in ACS patients compared to the CHA2DS2-VASc score of 1 or lower. Despite its lower predictive accuracy compared to the GRACE risk score, CHA2DS2-VASc score can still be used in practical situations as an alternative scoring system in predicting in-hospital mortality in ACS patients, especially in primary health care settings located in rural areas that lack the diagnostic facilities.This article has a related Erratum.